2020
DOI: 10.1021/acs.jnatprod.0c00675
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxy Pyridones from Heterologous Expression and Cultivation of the Native Host

Abstract: 4-Hydroxy pyridones are a class of fungi-derived polyketide–nonribosomal peptide products featuring a core of 4-hydroxy-2-pyridone which have a wide range of biological activities. Genome mining of in-house strains using polyketide synthase–nonribosomal peptide synthase as a query identified an endophyte Tolypocladium sp. 49Y, which possesses a potential 4-hydroxy pyridone biosynthetic gene cluster. Heterologous expression in Aspergillus oryzae NSAR1 revealed that this gene cluster is functional and able to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…22,26,27,46−48 AdpE, HarG, ApnG, and TolB have been shown to exhibit three different activities: one is to form 2-pyridone molecules, similar to TenA, another is hydroxylation at the β-carbon of the amino acid moiety, and the last one is oxidative dephenylation (Figure 5). 28,49,50 MacC does not clade with the other P450 enzymes based on the analysis. The phylogenetic analysis suggested that P450 enzymes encoded in PKS-NRPS-containing BGCs have evolved to perform different oxidative functions to generate structural and functional diversity.…”
Section: ■ Materials and Methodsmentioning
confidence: 88%
“…22,26,27,46−48 AdpE, HarG, ApnG, and TolB have been shown to exhibit three different activities: one is to form 2-pyridone molecules, similar to TenA, another is hydroxylation at the β-carbon of the amino acid moiety, and the last one is oxidative dephenylation (Figure 5). 28,49,50 MacC does not clade with the other P450 enzymes based on the analysis. The phylogenetic analysis suggested that P450 enzymes encoded in PKS-NRPS-containing BGCs have evolved to perform different oxidative functions to generate structural and functional diversity.…”
Section: ■ Materials and Methodsmentioning
confidence: 88%
“…Fungal 4-hydroxy pyridones are polyketide-NRP compounds with diverse structures and biological activities [114]. The biosynthesis of these compounds is initiated by the PKS-NRPS and a trans-acting enoyl reductase (ER) to yield a pentacyclic intermediate, acryltetramic acid.…”
Section: -Hydroxy Pyridonesmentioning
confidence: 99%
“…However, we had not observed the production of such metabolites from the wild type of A. felina SYSU-MS7908, suggesting that this BGC might be silent. We decided to activate this BGC by heterologous expression in A. oryzae NSAR1 as it is a robust host to mine fungal natural products [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%